استخدام أساليب التقويـم التربـوي الحديثـة ودورها في جـودة التعليـم - غرايسة, احمد; عواريب, لخضر (جامعة الوادي - University of Eloued, 2021)
تهدف الدراسة الحالية إلى التعرف على واقع استخدام الأساليب الحديثة للتقويم التربوي في مجال علوم التربية ودوره في تجويد عملية التعليم بصفة عامة ومعرفة أهم التوجهات الحديثة للتقويم التربوي واستعراض الاستراتيجيات البديلة ، من اجل تطوير وتحسين العملية التعليمية في ميدان علوم التربية، و من خلال هذه الدراسة سوف نتطرق إلى التعرف عل أهم أساليب التقويم التربوي، المستخدمة في توجهات التقويم التربوي الحديث ، مع ذكر الايجابيات والسلبيات ، وتوضيح الأسس التي يقوم عليها التقويم الناجح، ومن ثم فان الحاجة ماسة لتطوير الأساليب المستخدمة في التقويم لمواكبة النظرة الحديثة في التعليم، وهذا ما تحققه أهداف التقويم الحديث أو ما يعرف كذلك ب التقويم الواقعي، حيث سوف نتطرق إلى مفهومه وتعريفه وتوضيح التحولات الناجمة عن المنظور الجديد للتقويم من الصيغة التقليدية إلى الاتجاه الحديث للتقويم.The current study aims to identify the reality of using modern methods of educational evaluation in the field of education sciences and its role in improving the education process in general and to know the most important modern trends for educational evaluation and review alternative strategies, in order to develop and improve the educational process in the field of education sciences, and through this study I will We address the identification of the most important methods of educational evaluation, used in the directions of the modern educational evaluation, with the pros and cons, and clarification of the foundations on which a successful evaluation is based, and then the need is dire to develop the methods used in the evaluation to keep pace with the modern view of education, and this is what the evaluation goals achieve, The talk or what is also known as the realistic calendar, where we will deal with its concept and definition and explain the shifts resulting from the new perspective of the calendar from the traditional formula to the modern direction of the calendar.
The use of modern educational evaluation methods and their role in the quality of education
مقال
Keywords: التقويم التربوي الحديث؛ أساليب التقويم التربوي؛ الجودة في التعليم; modern educational calendar; educational evaluation methods; quality in education.